Key processes controlling the variability of the summer marine CO2 system in Fram Strait surface waters - Aguado Gonzalo, Fernando; Stokowski, Marcin; Koziorowska-Makuch, Katarzyna; Makuch, Przemysław; Beszczyńska-Möller, Agnieszka; Kukliński, Piotr; Kuliński, Karol (Frontiers in Marine Science, 2024)
The aim of this study was to decouple and quantify the influence of various biological and physical processes on the structure and variability of the marine carbonate system in the surface waters of the eastern part of the Fram Strait area. This productive region is characterized by its complex hydrographic and sea ice dynamics, providing an ideal set up to study their influence on the variability of the marine carbonate system. Different variables of the marine CO2 system: Total Alkalinity (TA), Dissolved Inorganic Carbon (DIC), partial pressure of CO2 (pCO2), and pH, were analysed together with temperature, salinity, sea ice extension, and chlorophyll a distribution during three consecutive summers (2019, 2020 and 2021), each of them having a unique oceanographic setting. The data revealed that TA and DIC are mostly controlled by the mixing of Atlantic water and sea ice meltwater. The combined effects of organic matter production/remineralization, calcium carbonate precipitation/dissolution, and air/sea CO2 gas exchange cause deviations from this salinity-related mixing. The scale of these deviations and the proportion between the effects observed for TA and DIC suggest interannual shifts in net primary production and dominant phytoplankton species in the area. These shifts are correlated with the sea ice extent and the spread of the Polar Surface Waters in the region. Net primary production is the main factor controlling the temporal and spatial variability of pH and pCO2 in the study area followed by the influence of temperature and, mixing of water masses expressed with salinity (seawater freshening). Surface waters of the the Fram Strait area were generally undersaturated in CO2. The lowest pCO2 values, coinciding with an increase in oxygen saturation, were observed in areas of mixing of Arctic and Atlantic-derived water masses. However, as shown for 2021, a reduction of the sea ice extent may induce a westward shift of the chlorophyll maximum, resulting in pCO2 increase and pH decrease in the eastern part. This indicates that sea ice extent and associated spread of Polar Surface Waters may be important factors shaping primary production, and thus pCO2 and pH, in the Fram Strait area.